2019
DOI: 10.1021/acs.jafc.9b04398
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dialkyldithiophosphates as Slow Hydrogen Sulfide Releasing Chemicals and Their Effect on the Growth of Maize

Abstract: Hydrogen sulfide is a key gasotransmitter for plants and has been shown to greatly increase their growth and survival in the presence of environmental stressors. Current methods for slowly releasing hydrogen sulfide use chemicals, such as GYY-4137, but these result in the release of chemicals not found in the environment, and chemicals used may lack structures that can be readily tuned to affect the rate of release of hydrogen sulfide. In this article, we describe the synthesis and slow release of hydrogen sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…In our prior work, we showed that the hydrolysis of dibutyldithiophosphate followed the mechanism shown in Figure 6 . 11 The first step of the hydrolysis was release of H 2 S, and the oxo intermediate was observed in the 31 P NMR spectra. No other intermediates were observed during this reaction for dibutyldithiophosphate.…”
Section: Results and Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In our prior work, we showed that the hydrolysis of dibutyldithiophosphate followed the mechanism shown in Figure 6 . 11 The first step of the hydrolysis was release of H 2 S, and the oxo intermediate was observed in the 31 P NMR spectra. No other intermediates were observed during this reaction for dibutyldithiophosphate.…”
Section: Results and Discussionmentioning
confidence: 98%
“…In our prior work, less than 3% of the dithiophosphates synthesized from fatty alcohols hydrolyzed after 35 days, and the results shown in Table 1 were consistent with that observation. 11 Of the 13 chemicals investigated, 8 of the dithiophosphates showed less than 3% hydrolysis, and 3 others were not soluble in water and not investigated. The potassium and triethylamine salts of 5 , 7 , and 13 were synthesized in attempts to improve their solubilities, but these salts were insoluble in water.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations